Comparative study of the antioxidant capacity in green tea by extraction at different temperatures of four brands sold in Colombia - Luz Stella RAMÍREZ ARISTIZABAL (Universidad de Antioquia, 2017)
Background: Tea (Camellia sinensis) is the most highly consumed beverage in the world in addition to water. The most common way of preparation is steeping it in hot or cold water.(1) In Colombia, this is a recent trend and the market is growing continuously. Objectives: The goal of this study is to compare the antioxidant characteristics of green tea of four brands sold in Colombia at room and hot-temperature in relation to brewing conditions. Methods: A set of four commercial brands of green tea (Oriental®, Lipton®, Hindú®, Jaibel®) was used in an aqueous extraction at two temperatures: Cold tea extract (25°C) and hot tea extract (80°C). Total polyphenol concentration (TPC) was determined by Folin-Ciocalteu method; Total flavonoid content (TFC) was determined using a spectrophotometric method and the antioxidant capacity was determined by means of both the scavenging of (DPPH) free radical assay, and the oxygen radical absorbance capacity (ORAC) assay. Finally, a method for quantifying the catechins present in tea extracts were developed applying high performance liquid chromatography (HPLC). Results: The TPC obtained was: 2.53 – 14.63 mg EAG / g sample for cold tea extract and 29.34 - 55.06 mg EAG/g sample for hot tea extract. The TFC was found to vary: 2.67 – 7.08 mg EC/ g sample for the cold tea extract and 5.43– 8.41 mg EC/ g sample for hot tea extract. A similar profile was observed for the antioxidant capacity determined by both methods: for cold tea extract: 22.36 – 41.29 mg TE /g sample for DPPH and 22.95 – 46.25 mg TE/g sample for ORAC. Similarly, for hot tea extract the following ranges were: 38.50 – 110.01 mg TE/g sample for DPPH and 23.40- 113.60 mg TE/g sample for ORAC. In general, the behavior of the two extraction concerning the assay, starting from the best followed this order: Oriental®> Lipton®> Hindú®> Jaibel®. The chromatographic profiles showed the presence of ten compounds. Conclusions: compounds with higher antioxidant capacity in comparison to extractions at room temperature. This results confirm the fact that extraction of green tea carried out with water at hot temperature leads to the formation of infusions rich in compounds with higher antioxidant capacity in comparison to extractions at room temperature..